Kajian Etnografi terhadap Legenda Asal Mula Tanaman Padi di Sumba - Konradus Doni Kelen; Paulus Ama Kamuri; Ariyanto Malo (Ideas Publishing, 2026)
This study aims to understand the construction of meaning and cultural practices of the Sumbanese people through the legend of the origin of rice, using an ethnographic approach. Grounded in ethnographic theory, particularly Clifford Geertz’s view of culture as a system of interpreted meanings, this research explores how the people of Sumba interpret the origin of rice as part of their symbolic structure and life rituals. The methods employed include participant observation, in-depth interviews with traditional elders, and documentation of oral traditions related to the legend. The findings reveal that the legend of the origin of rice contains a comprehensive ethnographic structure encompassing the eight components acronymized as SPEAKING: S (Setting and Scene), P (Participants), E (Ends; purposes and goals), A (Act Sequences), K (Key; tone or spirit of the act), I (Instrumentalities), N (Norms of interaction and interpretation), and G (Genres). Through the ethnographic lens, this legend is understood as a cultural instrument that reflects collective identity and strengthens social cohesion within the community. It is hoped that this study contributes to the preservation of intangible cultural heritage and enriches the field of cultural literary studies.